The Tragedy in the Story of Rostam and Sohrab in Ferdowsi’s Shahnameh - Ebrahimi, Mokhtar; Taheri, Abdollah (Journal of History Culture and Art Research, 2017)
Tragedy is a stunning example of confrontation between man and nature along with sadness and consequently fate and life. In tragedy, usually one person (hero) is in the center of the story and all of the stories come together to make the inevitable fate happen for that hero. This inevitable fate is usually along with death or a tragic end which occurs for the hero. The purpose of poet in tragedy is illustration of an advice for readers after death of the hero. In this article, we have tried to review various aspects of tragic story of Rostam and Sohrab and the way the Master of Tous makes his audience and fans aware of passage of time and the eternal destiny using analytical descriptive method. Undoubtedly, what the ancient Greeks, especially Aristotle have proposed as a definition for tragedy as, is in some cases different from Ferdowsi's view but there is a close consistency between the nature of tragedy and the base of tragedy of Rostam and Sohrab and definition of tragedy.